2014
DOI: 10.1016/j.neuroscience.2014.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Inter-hemispheric functional connectivity changes with corpus callosum morphology in multiple sclerosis

Abstract: Multiple sclerosis (MS) affects myelin sheaths within the central nervous system, concurring to cause brain atrophy and neurodegeneration as well as gradual functional disconnections. To explore early signs of altered connectivity in MS from a structural and functional perspective, the morphology of corpus callosum (CC) was correlated with a dynamic inter-hemispheric connectivity index. Twenty mildly disabled patients affected by a relapsing-remitting (RR) form of MS (EDSS ≤ 3.5) and 15 healthy subjects underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 35 publications
4
15
0
Order By: Relevance
“…In fact, we found a significant moderately positive correlation between CCA and global sHIC, demonstrating a structure-function relationship between inter-hemispheric connectivity and callosal atrophy in MS. This finding extends previous work performed using volumetric methods [Zhuo et al, 2013] and confirms results found using EEG [Zito et al, 2014]. Future work should extend these findings to larger populations of MS subjects, including those with longer disease durations and a greater degree of disability.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, we found a significant moderately positive correlation between CCA and global sHIC, demonstrating a structure-function relationship between inter-hemispheric connectivity and callosal atrophy in MS. This finding extends previous work performed using volumetric methods [Zhuo et al, 2013] and confirms results found using EEG [Zito et al, 2014]. Future work should extend these findings to larger populations of MS subjects, including those with longer disease durations and a greater degree of disability.…”
Section: Discussionsupporting
confidence: 90%
“…Our result is consistent with previous findings showing decreased interhemispheric FC at rest in people with MS using magnetoencephalography (MEG) or encephalography (EEG) (Cover et al 2006;Zito et al 2014). It is also consistent with results from studies using TMS finding that the interhemispheric inhibition between motor cortices mediated by slowly conducting fibres passing through the corpus callosum was deficient (Schmierer et al 2000;Schmierer et al 2002).…”
Section: Hc Vs MIsupporting
confidence: 93%
“…Asterisks denoted the significance of the level of accuracy with ** for p < 0.01 and *** for p < 0.001 structure providing interhemispheric communication between grey matter structures, can be profoundly damaged in MS (Evangelou et al 2000;Gean-Marton et al 1991) even when the T2 lesions only consisted around 1.4 % of the callosal volume (Ozturk et al 2010). Damage in the corpus callosum has been previously linked to both weakened interhemispheric FCs (Zito et al 2014) and physical disability (Audoin et al 2007;Llufriu et al 2012;Ozturk et al 2010;Yaldizli et al 2011). In addition, white matter lesions within the hemispheres affecting any fibres connected with the corpus callosum may also influence the functional connectivity.…”
Section: Hc Vs MImentioning
confidence: 99%
“…In addition, we tested patients with relapsing-remitting multiple sclerosis (RRMS) in the identical BTC protocol. We chose multiple sclerosis as a model disease of callosal damage, given the findings of frequent and early callosal affection in RRMS (Evangelou et al 2000a, b;Pelletier et al 2001;Zito et al 2014). We have shown previously, that impaired S-IHI along with reduced FA-hCMF is already present in the earliest stages of RRMS (Wahl et al 2011), but the behavioral implications of these findings have not been tested.…”
Section: Introductionmentioning
confidence: 99%